Process study and CO2 emission reduction analysis of coal liquefaction residue fluidized bed pyrolysis - Tian, Bo; Gao, Junhu; Guo, Qiang; Zhu, Xiaoming; Zhang, Hao; Zhu, Wei; Hao, Xu; Yang, Chaohe; Yang, Yong; Li, Yong-Wang (Frontiers in Energy Research, 2022)
Direct coal liquefaction process usually produces liquefaction residue of about 30% of its coal feed. The effective utilization of coal liquefaction residue (CLR), which contains about 80% organic matter, is of great significance to improve the oil yield of the direct liquefaction process and to reduce the amount of pollution emission of this oil-containing organic solid waste. In this paper, the CLR fluidized bed pyrolysis process was studied through fluidized bed reactor pyrolysis experiment and steady-state thermal analysis. The characteristics of CLR was firstly analyzed, and then the pyrolysis experiment was conducted in a fluidized bed reactor system. The experiment results show that the oil yield is 34.81% at 540 ℃ for an ash free feedstock using fluidized bed pyrolysis reactor. Based on the pyrolysis experimental data and Aspen Plus software platform, the fluidized bed pyrolysis reactor, fractionation column, coke burner, gasifier, and other equipment were modeled to compare four different process schemes. As CLR pyrolysis is an endothermic reaction, and its heat is usually supplied by coke combustion which brings much CO2 emissions. Case studies of the pyrolysis process was performed in detail in order to reduce CO2 emissions. Thermal efficiency, carbon efficiency, solid waste discharge, as well as CO2 emissions of the different schemes were compared and a flexible fluidized pyrolysis (FFP) process coupled with water electrolysis was proposed. The introduction of green hydrogen and green oxygen to the process can realize near-complete utilization of carbon and hydrogen elements in the CLR, and produce high quality liquid fuels and syngas (for further chemicals synthesis), and this new process can achieve almost near-zero CO2 emission in the entire unit. This process principle can also be applied to the CO2 emission reduction of organic solid waste pyrolysis, catalytic fluid cracking, fluid coking and so on.